The ChEMBL database in 2017. Issue Volume 45:Issue D1(2017) (28th November 2016) - Gaulton, Anna; Hersey, Anne; Nowotka, Michał; Bento, A. Patrícia; Chambers, Jon; Mendez, David; Mutowo, Prudence; Atkinson, Francis; Bellis, Louisa J.; Cibrián-Uhalte, Elena; Davies, Mark; Dedman, Nathan; et al.
Abstract: ChEMBL is an open large-scale bioactivity database (https://www.ebi.ac.uk/chembl ), previously described in the 2012 and 2014 Nucleic Acids Research Database Issues. Since then, alongside the continued extraction of data from the medicinal chemistry literature, new sources of bioactivity data have also been added to the database. These include: deposited data sets from neglected disease screening; crop protection data; drug metabolism and disposition data and bioactivity data from patents. A number of improvements and new features have also been incorporated. These include the annotation of assays and targets using ontologies, the inclusion of targets and indications for clinical candidates, addition of metabolic pathways for drugs and calculation of structural alerts. The ChEMBL data can be accessed via a web-interface, RDF distribution, data downloads and RESTful web-services.